Monochromatic Integral Image Identification Based on Adaboost and Viola-Jones Classifier - Kathiravan.T; Kolanchinathan V P; Dinesh Kumar T R; Harini.L; Keerthana.P; Mahalakshmi.E; Sivaram (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
In every sector, trustworthiness, and authentication played important roles. Technology understanding growth causes an increase in crime. Crime suspects are difficult to distinguish from members of the general population. Face recognition technology may be useful in identifying the perpetrators of a crime. In this study, the viola-Jones algorithm and the LPBH algorithm (Local Pattern Binary Histogram) were used to forecast the occurrence of crimes. The viola-jones algorithm was used to collect the statistics on crime. According to the characteristics of the face, these data were categorized and trained by Adaboost, and the findings were saved in a database. The final step was to determine the criminal suspects by comparing the input data to the previously stored images.